Rethinking the body in global politics : bodies, body politics and the body politic in a time of pandemic - Purnell, Kandida (Abingdon, Oxon ; New York, NY : Routledge, 2021)
'This book rethinks the body in global politics and the particular roles bodies play in our international system, foregrounding processes and practices involved in the continually contested (re/dis)embodiment of both human bodies and collective bodies politic. Purnell provides a new, innovative, and detailed theory of bodily (re)making and un-making that shows how bodies are simultaneously (re)made and moved and (re)make and move other bodies and things. Presented in the form of reflective/reflexive and theoretically innovative essays, the book explores: bodies in general and their precarious, excessive, ontologically insecure, and emotional facets; the fleshing out of contemporary necro(body)politics; and the visual-emotional politics embodied through the COVID-19 pandemic'--
Rethinking the body in global politics : an introduction -- On bodies -- Body politics -- The body politic -- Conflicted bodies -- Rethinking the body in global politics : some conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Human body -- Political aspects; International relations -- Social aspects; International relations -- Philosophy; Biopolitics; State governments and international relations; World politics -- 21st century